Blood Clotting, Plasma Kinins and Fibrinolysis - Gjønnæss, H; Stokmorken, H (Thrombosis and Haemostasis, 1970)
In plasma of women on oral contraception a marked activation of factor VII takes place, when stored overnight at low temperatures. This activation is dependent on factor XII, and evidence is presented that it may be mediated by the plasma kinin system.